1986
DOI: 10.1007/bf01639003
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of cardenolides inOncopeltus fasciatus: Morphological and physiological adaptations

Abstract: The morphological and physiological adaptations associated with sequestration of cardenolides by the lygaeidOncopeltus fasciatus are summarized and discussed. Cardenolides are efficiently accumulated inO. fasciatus; however, the insect does not appear to suffer any physiological cost as a result of handling large amounts of these plant toxins. Morphological adaptations of the insect include a modified integument composed of a double layered epidermis with an inner layer (the dorsolateral space) specialized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 58 publications
2
63
0
1
Order By: Relevance
“…The shape depends on many factors, including the predator's ability to detect the toxin at different concentrations and its susceptibility to the toxin; in addition, it will depend on the tissue(s) in which the prey store the toxin and on whether the toxin is excreted in response to predators [9,[41][42][43][44][45]. Since little is currently known about the shape of this function, some hypothetical examples have been explored ( figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The shape depends on many factors, including the predator's ability to detect the toxin at different concentrations and its susceptibility to the toxin; in addition, it will depend on the tissue(s) in which the prey store the toxin and on whether the toxin is excreted in response to predators [9,[41][42][43][44][45]. Since little is currently known about the shape of this function, some hypothetical examples have been explored ( figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the monarch butterfly, Danaus plexippus, and the large milkweed bug, Oncopeltus fasciatus, in vitro assays showed that these species possess Na,K-ATPases that have a dramatically lowered binding affinity to cardenolides (ouabain) (19)(20)(21)(22). Molecular investigations later demonstrated that this insensitivity may be explained in the monarch butterfly, at least in part, by an amino acid substitution of asparagine for histidine at position 122 (N122H) in the first extracellular loop of the Na,KATPase (19,23).…”
mentioning
confidence: 99%
“…We detected a unique doublelayered epidermis in O. fasciatus and showed that cardenolides accumulated in the innermost layer, with the integument having special pores for their release. We undertook an experimental investigation of a number of special physiological adaptations in O. fasciatus associated with cardenolide uptake, regulation, and release (56,107,108), including the ability of the Malpighian tubules to excrete ouabain (53), and we showed the presence of ouabainresistant Na, K-ATPases in this insect (55).…”
Section: Wwwannualreviewsorg • Life and Research Of An Entomologistmentioning
confidence: 99%